Formulation of VCO (Virgin Coconut Oil) Massage Oil with Red Ginger (Zingiber Officinale Var Rubrum) Combination as A Muscle Pain Relief - Hakim, Reny Anggriany; Rahmasiah, Rahmasiah; Sulaiman, Sulaiman; Sabil, Sabil (Journal of Pharmaceutical and Health Research, 2025)
Traditional medicine used by people today, sometimes uses synthetic materials to make preparations, one of which is massage oil. This has long been an inseparable part of the Indonesian nation which is believed to provide benefits for health and beauty. For centuries in Indonesia, the term massage or urut has long been known. So that massage oil made from natural ingredients is widely in demand by the Indonesian people as a traditional medicine used for relaxation, relieving muscle pain, and relaxing muscles. Purpose of the study To find out how to make a VCO (Virgin Coconut Oil) massage oil formulation combined with red ginger (Zingiber Officinale Var Rubrum) as a muscle pain reliever. The research method is experimental by testing each formula with organoleptic, pH, homogeneity, and stability tests. The results of organoleptic testing of each Formula: f1 bright yellow color, has VCO and a little ginger, runny texture, f2 golden yellow color, has VCO and red ginger, runny texture, f3 golden yellow color, has VCO and red ginger odor, slippery texture. The pH value of f1 does not meet the pH standard while f2 and f3 meet the pH standard. Homogeneity testing of all formulas meets the standard. Stability testing of all formulas meets the stability standard.